2009
DOI: 10.1007/s10620-009-0788-2
|View full text |Cite
|
Sign up to set email alerts
|

Biliary Sphincter of Oddi Dysfunction Type I Versus Occult Biliary Microlithiasis in Post-cholecystectomy Patients: Are They Both Part of the Same Clinical Entity?

Abstract: We speculate that biliary sphincter of Oddi dysfunction type I and symptomatic migrating biliary microlithiasis may be part of the same disease process. A retrospective analysis of prospectively collected data was carried out using procedure and diagnosis codes during the period of 1997-2006. Seventeen patients (age 51 +/- 17; 94% women) with prior cholecystectomy, right upper quadrant/epigastric abdominal pain, elevated liver enzymes, dilated biliary ducts seen on ultrasound/CT scan were identified. The patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
3
0
3
Order By: Relevance
“…Nine of 17 (53%) patients had concurrent microlithiasis in their bile, and all responded similarly well to EBS. 13 This study speculated that the passing of stones leads to fibrosis and scarring of the ampulla of vater, likely to be part of the pathogenesis of Type 1 SOD. An earlier and larger prospective study by Quallich et al had found only a 5% prevalence of microlithiasis in 60 patients with Type II and Type III SOD with both normal and abnormal manometry, though these results did not meet statistical significance.…”
Section: Biliary Microlithiasismentioning
confidence: 95%
See 1 more Smart Citation
“…Nine of 17 (53%) patients had concurrent microlithiasis in their bile, and all responded similarly well to EBS. 13 This study speculated that the passing of stones leads to fibrosis and scarring of the ampulla of vater, likely to be part of the pathogenesis of Type 1 SOD. An earlier and larger prospective study by Quallich et al had found only a 5% prevalence of microlithiasis in 60 patients with Type II and Type III SOD with both normal and abnormal manometry, though these results did not meet statistical significance.…”
Section: Biliary Microlithiasismentioning
confidence: 95%
“…The second is sphincter of Oddi dyskinesia, referring to a functional abnormality of the sphincter leading to intermittent obstruction, perhaps due to still unknown neuro-hormonal disturbances. 13 Stenosis is thought to occur in type 1 SOD, inferred from its predictable response to sphincterotomy, whereas dyskinesia is thought to occur in type 2 and type 3 SOD, which are less understood.…”
Section: Sphincter Of Oddi Dysfunctionmentioning
confidence: 99%
“…Третий уровень предусматривает подготовку по специализированной медицинской помощи, которую специалисты проходят в последипломном образовании . Возможны межпрофессиональные программы со специальными модулями для различных специалистов [37] . В настоящее время в Украине функционируют 2 центра паллиативной и хосписной помощи (ПхП), 7 хосписов, 60 отделений на 1,5 тыс .…”
Section: микроорганизмыunclassified
“…В 10-20% случаев симптомы билиарной боли возникали в этой группе и до прове-дения операции [22], что может быть связано с наличием других нарушений со стороны ЖКТ, таких как синдром раздраженной кишки и/или неязвенная диспепсия. Кроме того, у многих паци-ентов может быть микролитиаз, который коррелирует с ДСО [23,24]. Несмотря на внедрение новых хирургических, фармакологи-ческих и физиотерапевтических методов лечения ДСО, эффек-тивность их остается низкой, что может быть связано с редким применением «золотого стандарта» диагностики ДСО -маноме-трии, для контроля эффективности терапии и индивидуального подбора лечения, а также с недостаточно изученным патофизио-логическим механизмом процесса пищеварения у пациентов, перенесших ХЭ [25][26][27][28].…”
Section: результаты и обсуждениеunclassified